Developing a business plan for language school in Spain - Dufek, Michal (2015)
The Master's Thesis analyses and evaluates the conditions for the development of language school in Alicante, Spain. Also, the thesis shows main concepts, as well as an illustration of specific steps and actions in a realistic business plan. Firstly, it introduces theoretical background of legal environment of Spain, business model and the business plan. Secondly, the thesis portrays the results of an empirical research conducted on the target audience that are together with the market analyses integrated into the business plan. At last, the business plan proposes marketing and financial projections that lead into final conclusion and recommendations for the business development.